2021
DOI: 10.1136/neurintsurg-2021-017502
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of endovascular thrombectomy for large versus medium vessel occlusions: a single-center experience

Abstract: BackgroundThe effectiveness and safety of endovascular thrombectomy (EVT) for medium vessel occlusions (MeVO) in the anterior intracranial circulation for patients with acute ischemic stroke (AIS) has yet to be definitively established. We compared outcomes in patients undergoing EVT for large vessel occlusion (LVO) versus those with MeVO.MethodsThis retrospective cohort study, using an intention to treat design, compared the 90-day modified Rankin Scale (mRS) score between 43 patients with MeVO and 199 with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…A recently published article demonstrated that in AIS patients, a larger 24-hour post-reperfusion infarct size was an independent predictor of poor functional outcome (49). Our study showed that WUS patients who underwent EVT had lower 24-hour post-reperfusion infarct volume.…”
Section: Discussionsupporting
confidence: 63%
“…A recently published article demonstrated that in AIS patients, a larger 24-hour post-reperfusion infarct size was an independent predictor of poor functional outcome (49). Our study showed that WUS patients who underwent EVT had lower 24-hour post-reperfusion infarct volume.…”
Section: Discussionsupporting
confidence: 63%
“…In fact, more than two attempts was an independent predictor of poor outcome at 90 days compared with three or more attempts, indicating that a lower number of thrombectomy attempts is tolerated in DVO compared with LVO. Notably, successful recanalization in this cohort was an independent predictor of good outcome in the DVO group; however, there was no correlation between the recanalization score (2B, 2C, vs 3) and clinical outcomes 26…”
Section: Discussionmentioning
confidence: 53%
“…The efficacy and safety of EVT for MeVO have been studied extensively, with most publications being retrospective and single-centre studies. [5][6][7][8][9][10][11][12][13] Thus, their findings might not be sufficiently applicable to real-world practice. As a result, a multicentre study is required to explore whether MeVO could benefit from EVT.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The efficacy and safety of EVT for MeVO have been studied extensively, with most publications being retrospective and single-centre studies 5–13. Thus, their findings might not be sufficiently applicable to real-world practice.…”
Section: Introductionmentioning
confidence: 99%